MAGNETIC PROPERTIES OF THE Fe2SiO4–Fe3O4 SPINEL SOLID SOLUTIONS - Yamanaka T.; Okita M. (My University, 2001)
Magnetic measurement of Fe3− x Si x O4 spinel solid solutions indicates that their Curie temperatures decrease gradually, but not linearly, from 851 to 12 K with increasing content of nonmagnetic ions Si4+. Magnetic hysteresis becomes more noticeable in solid solutions having a larger content of Fe2SiO4. Saturation magnetizations of Fe3− x Si x O4 samples increase up to x=0.357 and they are easily saturated in the field of H=0.1 T. However, magnetization of the sample of x=0.794 does not approach saturation even at high field of H=7.0 T and has a large coercive force. The Si4+ disordered distribution is confirmed to be tetr[Fe3+ 1− x + x t Si4+ x (1− t )] octa[Fe2+ 1+ x Fe3+ 1− x − x t Si4+ x t ] O4 by the spin moment, which is consistent with site occupancy obtained from X-ray crystal structure refinement. Their molecular magnetizations would be expressed as M B={4(1+x)+10xt}μB as functions of composition parameter x and Si4+ ordering parameter t of the solid solution. The sample of x=0.794 is antiferromagnetic below the Néel temperature, mainly due to the octahedral cation interaction M O–M O, while both M T–M O and M O–M O interactions induce a ferrimagnetic property. Concerning magnetic spin configuration, in the case of x>0.42, the lowest dɛ level becomes a singlet, resulting in no orbital angular momentum.
Keywords: FE3-x SIx O4 SPINEL SOLID SOLUTION; SATURATION MAGNETIZATION; MAGNETIC HYSTERESIS; BOHR MAGNETON; CURIE TEMPERATURE